Analisis Kepuasan Konsumen Terhadap Produk Abon Ikan Tuna Di Kub Kembangbaru Nangahure Kecamatan Alok Barat - Maria Yohana Wonga (Peneliti.net, 2022)
Consumer satisfaction is the overall attitude that consumers show towards goods and services after they acquire and use them. If the quality is far below expectations, it will experience emotional dissatisfaction. Consumer satisfaction includes the difference between expectations and perceived performance or results. The purpose of this study is to find out how the level of consumer satisfaction with tuna shredded products in kub new flowers nangahure. This research is quantitative research. Respondents from this study were consumers who bought and consumed 30 tuna shreds. Data collection using kuisone. Data analysis is performed with simple linear regression analysis. The results of this study show that: consumer satisfaction has a positive and significant effect on production results with a value of t count > t table and a significant value smaller than 0.05 so that Hi is rejected and Ho is accepted. This shows that consumer satisfaction has a positive and significant influence on tuna shredded production. Between the consumer satisfaction variable (X) and the variable tuna production result (Y) has a strong correlation relationship because it has a correlation value of 0.688 between (0.60-0.799).